2006
DOI: 10.1044/1059-0889(2006/015)
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition in Noise in Children With Cochlear Implants While Listening in Bilateral, Bimodal, and FM-System Arrangements

Abstract: Children's speech-in-noise thresholds did not improve when providing input to the second side with a CI or an HA relative to a single CI. However, children with CIs had better speech recognition in noise with the use of an FM system on one or both sides relative to the conditions with no FM system. Binaural conditions with a single FM receiver on the second CI or HA yielded significantly poorer performance than any other FM condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 40 publications
5
86
0
8
Order By: Relevance
“…These results support the indication of the FM system described in several international studies, which point to the device as an essential resource for hearing impaired children, especially in the school environment (1,9,(20)(21)(22)(23)(24)(25) .…”
Section: Benefit Of the Fm Systemsupporting
confidence: 75%
See 1 more Smart Citation
“…These results support the indication of the FM system described in several international studies, which point to the device as an essential resource for hearing impaired children, especially in the school environment (1,9,(20)(21)(22)(23)(24)(25) .…”
Section: Benefit Of the Fm Systemsupporting
confidence: 75%
“…Although these devices are determinant for these abilities, their users may present difficulties in understanding speech in certain situations and environments. The presence of competitive noise in the environment and factors such as reverberation and distance from the sound source may impair the relationship between the speech signal and noise (1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do HINT Brasileiro não disponibilizar uma versão do teste para crianças como em outras Línguas (Hearing in Noise Test for Children /HINT-C) (23,24), muitos estudos utilizam o HINT com essa população (6,(25)(26)(27), visto que o material de fala desenvolvido para o teste busca metodologicamente controlar as variáveis que podem influenciar a inteligibilidade de fala para adultos e crianças (11).…”
Section: Discussionunclassified
“…Studies have shown that the adverse effects of noisy environments may be reduced by means of the use of advanced technological systems associated with the CI. New pre-processing strategies, Frequency Modulation (FM) systems, directional microphones, larger Input Dynamic Ranges (IDR) are example of technological resources currently available to attempt to minimize the effects of noise for the speech performance of implanted children 22,23 . Considering such technological innovation and resources, it is expected that children implanted with more current devices may have a better auditory performance in day-to-day situations.…”
Section: Discussionmentioning
confidence: 99%